Molecular Identification of Human Hookworm Infections in Economically Disadvantaged Communities in Peninsular Malaysia - Romano, Ngui; Lee, Soo Ching; Tan, Tiong Kai; Muhammad Aidil, Roslan; Yvonne Ai, Lian Lim (The American Society of Tropical Medicine and Hygiene, 2012)
Species identification of human hookworm infections among eight communities in rural areas of Peninsular Malaysia was determined during 2009–2011. Fecal samples were examined by microscopy and subsequently, the internal transcribed spacer 2 and 28S ribosomal RNA region of Necator americanus and Ancylostoma spp. were sequenced. Overall, 9.1% (58 of 634) were identified positive by microscopy for hookworm infection, and 47 (81.0%) of 58 were successfully amplified and sequenced. Sequence comparison found that N. americanus (87.2%) was the most predominant hookworm identified, followed by Ancylostoma ceylanicum (23.4%). No A. duodenale infection was detected in this study. Detection of A. ceylanicum in humans highlighted the zoonotic transmission among humans living near dogs. Thus, implementation of effective control measures for hookworm infections in future should seriously consider this zoonotic implication.